Obstetric Inpatient and Ultrasound Clinical Personnel Absences during the COVID-19 Pandemic in New York City - Spiegelman, Jessica; Bertozzi-Villa, Clara; D'Alton, Mary E.; Aubey, Janice J.; Fuchs, Karin; Goffman, Dena; Gyamfi-Bannerman, Cynthia; Miller, Russell; Robinson, Kenya E.; Sheen, Jean-Ju; Simpson, Lynn L.; Valderrama, Natali E.; Wen, Timothy; Zork, Noelia; Friedman, Alexander M. (American Journal of Perinatology, 2021)
Objective To review obstetric personnel absences at a hospital during the initial peak of coronavirus disease 2019 (COVID-19) infection risk in New York City from March 25 to April 21, 2020.Study Design This retrospective study evaluated absences at Morgan Stanley Children's Hospital. Clinical absences for (1) Columbia University ultrasonographers, (2) inpatient nurses, (3) labor and delivery operating room (OR) technicians, (4) inpatient obstetric nurse assistants, and (5) attending physicians providing inpatient obstetric services were analyzed. Causes of absences were analyzed and classified as illness, vacation and holidays, leave, and other causes. Categorical variables were compared with the chi-square test or Fisher's exact test.Results For nurses, absences accounted for 1,052 nursing workdays in 2020 (17.2% of all workdays) compared with 670 (11.1%) workdays in 2019 (p < 0.01). Significant differentials in days absent in 2020 compared with 2019 were present for (1) postpartum nurses (21.9% compared with 12.9%, p < 0.01), (2) labor and delivery nurses (14.8% compared with 10.6%, p < 0.01), and (3) antepartum nurses (10.2% compared with 7.4%, p = 0.03). Evaluating nursing assistants, 24.3% of workdays were missed in 2020 compared with 17.4% in 2019 (p < 0.01). For ultrasonographers, there were 146 absences (25.2% of workdays) in 2020 compared with 96 absences (16.0% of workdays) in 2019 (p < 0.01). The proportion of workdays missed by OR technicians was 22.6% in 2020 and 18.3% in 2019 (p = 0.25). Evaluating attending physician absences, a total of 78 workdays were missed due to documented COVID-19 infection. Evaluating the causes of absences, illness increased significantly between 2019 and 2020 for nursing assistants (42.6 vs. 57.4%, p = 0.02), OR technicians (17.1 vs. 55.9%, p < 0.01), and nurses (15.5 vs. 33.7%, p < 0.01).Conclusion COVID-19 outbreak surge planning represents a major operational issue for medical specialties such as critical care due to increased clinical volume. Findings from this analysis suggest it is prudent to devise backup staffing plans.Key Points
Keywords: COVID-19; obstetric staff; operations; pandemic